SINTESIS DAN KARAKTERISASI β-TRICALCIUM PHOSPHATE DARI CANGKANG TELUR AYAM DENGAN VARIASI SUHU SINTERING - Kiagus Dahlan (Jurnal Biofisika, 2012)
β-tricalcium phosphate includes a group of calcium phosphate compounds. β-Tricalcium phosphate was obtained by the chemical reaction of calcium oxide and phosphoric acid using the precipitation method on the solution temperature at 50oC and its sintering temperature varies, which are 800oC, 900oC, 1000oC, 1100oC, 1200oC, and 1300oC. In this study, calcium oxide based on chicken eggshells The characterization results which using x-ray diffractometer shows that the most optimum β-tricalcium phosphate which is fabricated at the sintering temperature of 1000oC with a percentage of 76,97%, the crystal size of 57,47 nm, the degree of crystallinity of 84,51%, while the characterization results which using fourier transform infrared spectrometer identify the existence of the hydroxyl group at the wavenumber of 3600- 3200 cm-1 and the phosphate group at the wavenumber of 1200-500 cm-1. Micrograph of scanning electron microscopy shows that β-tricalcium phosphate shaped with a size of 0,6 µm